Calculating and measuring contact angles of Zn–4.5%Al melt on Ceria substrates. (November 2015) - Zhou, H.; Gu, M.; He, X.; Bai, Y.; Wang, Z.
Abstract : The wetting behaviour of Zn−4.5%Al melts (ZA) on Ceria substrates was analysed in terms of surface tension, contact angle and chemical reactivity. Equilibrium equation calculating stable contact angle between high-energy interfaces was presented. The apparent contact angles of ZA melts on the untreated and treated CeO2 -baseplates in argon were measured by the sessile drop method and the influence of a carbonisation layer on wetting was discussed. The results show that simplified Good–Girifalco equation can be used to predict contact angles of metal/ceramic couples, and that, from classical thermodynamic point of view, reactions between the carbonisation layer and zinc oxide may take place at the interface, which promotes the wetting. As a result, the contact angle decreases from 111.6° to 87.6° and ZA liquid can wet CeO2 substrate.